PENERAPAN TEKNOLOGI PRODUKSI DAN STRATEGI PEMASARAN PADA UMKM JAHE INSTAN JM HAMKA - Sukmawati, Wati; Sunaryo, Hadi; Heriansyah, Daram (Universitas Muhammadiyah Tapanuli Selatan, 2021)
UMKM JM HAMKA is a UMKM (micro, small and medium enterprises) that produces instant ginger powder in Indramayu. So far, the processing of instant ginger is done traditionally so that the number of production and product marketing is very limited. This community partnership program activity was carried out to overcome these partner problems by holding mentoring training, product marketing management training, and procurement of appropriate machines (ginger recrystallization machine, ginger grater machine, ginger washing machine). Later, partners were able to manage their business better. In this activity, the method used in this activity is a questionnaire, and practice by assisting in using technological tools in processing ginger powder and training in marketing management. All of these activities are carried out online to prevent the spread of the Covid-19 virus. Forty-two participants attended this training and mentoring activity. Next, the data was processed using excel and obtained data that as many as 95.2% of participants were interested in this activity, while the rest did not answer the questionnaire given, besides the effectiveness of production can save time as much as 30% and sales also increase by 35%. The output target in this activity is that partners can produce instant ginger of good quality and in larger quantities to reach a wider market, and partners are expected to be able to manage financial management and marketing so that the income generated by partners also increases.